Global awareness of undergraduates in private higher educational institutions in Malaysia - K Rajanthran, Subashini (2023)
The purpose of this study is to investigate global awareness (GA) among undergraduates in private higher educational institutions (PHEIs) in Malaysia. This mixed-methods study examines GA among undergraduates in PHEIs, compares GA between the local and international undergraduates, identifies their source of GA and finally, assesses their perspectives on the inclusion of GA in the higher education curriculum. Using surveys and focus groups interviews, the study finds low GA amongst the students participating in the study, that their main sources of GA are from outside their PHEIs, and that both local and international undergraduates support the inclusion of GA in the curriculum.